Promotion of knowledge about the indigenous population: Interventions to bring together indigenous and non-indigenous children - Moretti, Christina Maria; Lira, Paula; Resende, Briseida (Guará Journal, 2024)
This paper presents the actions and reflections carried out in the project “Correspondence between different Brazilian childhood experiences” carried out in the years 2017 and 2018 with children from 4 to 6 years of age that involved teaching, the re-search and university extension in the exchange of correspondence between children of São Paulo - SP and São Gabriel da Cachoeira - AM. It was carried out through circles of conversa-tions and photographic and graphic records on the daily lives of children and documentary and bibliographical surveys on indigenous communities in Brazil. This action contributed to the change of perspective of children about indigenous peoples and the continuing education of educators involved in the process.